Acolher entre línguas: representações linguísticas em políticas de acolhimento para migrantes venezuelanos em Roraima - Cora Elena Gonzalo Zambrano (2021)
This research is inserted in the field of Indisciplinary Applied Linguistics and Transgressive Applied Linguistics (MOITA LOPES, 2006), having as scenario the forced migration for survival (BETTS, 2010) of Venezuelan citizens in Roraima, specifically in the municipalities of Boa Vista and Pacaraima. The main objective is to understand the links between representations about languages and language policies at work in actions and services aimed at Venezuelans in Roraima, as well as to identify how language rights (ABREU, 2020) are addressed in these policies. The specific objectives are: (i) to identify and analyze how the language rights of migrants are addressed in documents concerning policies for the welcome of Venezuelans in Roraima; (ii) to identify and analyze the representations about languages by those involved in the implementation of policies for Venezuelan migrants in the state; (iii) identify and analyze the representations about languages by Venezuelans who participate in policies for the welcome of migrants in Roraima; (iv) understand how these representations impact the implementation processes of the welcoming policies; (v) to discuss the extent to which the linguistic rights of migrants are respected in these welcoming policies. To achieve these goals, I used the qualitative and interpretativist methodology, with extensive bibliographic, documentary and field research. The generation of records occurred in three different phases: the first, with the specific documentary survey on the actions of reception carried out from the increased demand of Venezuelans in Roraima. The second, through semi-structured interviews with civil servants from the federal, state and municipal spheres (Boa Vista and Pacaraima). The last step was the execution of a focus group activity, whose target audience were students of a Portuguese as a Welcome Language course. In this phase, I adopted narrative research, through the analysis of oral narratives recorded during the focus group. The results point to the erasure of forced migrant subjects and their linguistic rights in some welcoming actions, as well as the presence of implicit and explicit language policies, both in official documents and in social practices. Among these representations is that of the Spanish language as being easy to understand and comprehend for everyone in the municipality of Pacaraima, bordering Venezuela, which neglects the need for a specific language policy in Spanish teaching-learning aimed at public servants who provide services to forced migrants for survival. Another representation is that it is the migrants who must learn the Portuguese language, which makes it difficult for some health professionals to welcome them. Resolutions of the State and Municipal Councils of Education show welcoming policies that may exclude some forced migrants in Roraima, making clear the conditional hospitality (DERRIDA, 2000) present in the welcoming policies. My proposal is to promote actions of welcome among languages, a welcome that respects the linguistic rights of forced migrants, encouraging welcome actions in the several languages that are part of the repertoire of these subjects, without allowing the Portuguese language to be the only or the most important one in this environment. Welcome among languages is also to value border thinking (MINGOLO, 2008, 2013) in the use of languages, encouraging translanguaging.